Degree of Islamic finance practices among the Malay Muslimpreneurs / Mohd Faizal P.Rameli ... [et al.] - P.Rameli, Mohd Faizal; Mohd Amin, Suhaida; Che Mana, Norajila; Mohd Arisa, Noorfazreen; Ab Wahab, Nor Azlina (Center for Islamic Philantrophy & Social Finance (CIPSF), 2020)
Malay Muslimpreneurs are at the forefront of Malaysia's liberalizing economy, keen innovators who have adopted the business and Islamic practices in the country. Malay Muslimpreneurs seek to promote economic development while also embedding economic practices within a framework of ethics and moral responsibilities deemed to be 'Islamic'. The purpose of this paper is to examine the degree of the Islamic finance practicing in determining the practices towards Islamic financing among the Malay Muslimpreneurs. A survey questionnaire is distributed to 95 respondents in Melaka, state of Malaysia. The study show that the Muslimpreneurs has not fulfill all the requirement needed by the Islamic Finance in their entrepreneurial activities. This study also show that only 72% of the respondent has practices at least 80% of Islamic Finance needs and the 28% of them were practiced about 65%- 79% of Islamic Finance needs.